Failure to apply for ethical approval for health studies in low-income countries - van Teijlingen, Edwin; Simkhada, Padam (Nepal Journal of Epidemiology, 2015)
On too many occasions researchers conduct public health and/or epidemiological studies in low-income countries without the appropriate in-country ethical approval. This article reflects on some of the underlying reasons for not applying for ethical approval. The piece concludes that we need to start by educating our (junior) researchers and research students about the importance of research ethics. We conclude with a number of recommendations for researchers, scientific journal editors and reviewers and ethical committees in high-income countries to bring the message home to researchers that ethical approval should be sought in low-income countries if and when required!